Expropriations, Property Confiscations and New Offshore Entities: Evidence from the Panama Papers - Ralph-C. Bayer; Roland Hodler; Paul A. Raschky; Anthony Strittmatter (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using the Panama Papers, we show that the beginning of media reporting on expropriations and property confiscations in a country increases the probability that offshore entities are incorporated by agents from the same country in the same month. This result is robust to the use of country-year fixed effects and the exclusion of tax havens. Further analysis shows that the effect is driven by countries with non-corrupt and effective governments, which supports the notion that offshore entities are incorporated when reasonably well-intended and well-functioning governments become more serious about fighting organized crime by confiscating proceeds of crime.
Keywords: H26; K42; 330; expropriations and confiscations; offshore entities; tax havens; Panama Papers